The revised JBI critical appraisal tool for the assessment of risk of bias for randomized controlled trials - Barker, Timothy Hugh; Stone, Jennifer C; Sears, Kim; Klugar, Miloslav; Tufanaru, Catalin; Leonardi-Bee, Jo; Aromataris, Edoardo; Munn, Zachary (JBI evidence synthesis, 2023)
JBI recently began the process of updating and revising its suite of critical appraisal tools to ensure that these tools remain compatible with recent developments within risk of bias science. Following a rigorous development process led by the JBI Effectiveness Methodology Group, this paper presents the revised critical appraisal tool for the assessment of risk of bias for randomized controlled trials. This paper also presents practical guidance on how the questions of this tool are to be interpreted and applied by systematic reviewers, while providing topical examples. We also discuss the major changes made to this tool compared to the previous version and justification for why these changes facilitate best-practice methodologies in this field.
Keywords: Bias; Humans; zkreslení výsledků (epidemiologie); Randomized Controlled Trials as Topic; lidé; randomizované kontrolované studie jako téma